FEEDING COTTON WITH MINERAL FERTILIZERS DURING THE GROWING SEASON IN THE CLIMATE OF ANDIJAN REGION (Лучшие интеллектуальные исследования, 2025)
Annotation. In the article, the norms of foliar application of the suspension prepared on the basis of urea fertilizers in the cotton variety “Andijan-35” grown in the conditions of typical gray soils of the Andijan region during the development periods of cotton, the effect on plant growth and development, cotton yield was determined.